Essentials of Employment Law / Eighth Edition - Lewis David; Sargeant Malcolm (Cipd (Chartered Institute of Personnel and Development), 2004)
The most authoritative textbook on employment law for all students of human resource management. Preface, The Sources and Institutions of Employment Law, Formation of the Contract of Employment (1): The Sources of Contractual Terms, Formation of the Contract of Employment (2): Implied Terms of Law, Recruitment and Selection, Pay Issues, Discrimination Against Employees on the Grounds of Sex; Sexual Orientation or Race, Discrimination on the Grounds of Disability and Religion or Belief and Age, Parental Rights, Health and Safety at Work, The Regulation of Working Time, Variation and Breach and Termination of the Contract of Employment at Common Law, Unfair Dismissal, Redundancy, Unfair Dismissal and Redundancy Claims, Continuity of Employment and Normal Working Hours and a Week's Pay, Human Rights and Data Protection, Information and Consultation, The Legal Framework of Collective Bargaining, Trade Unions and Their Members, Liability for Industrial Action, Index.